The Role of Internet Media in Enhancing MSME Sales in Tanjung Balai City - Efendi, Nasrul; Pelawi, Pioner; Ginting, Mbayak; Ginting, Sugianta Ovinus; Siagian, Hanny; Lubis, Tya Wildana Hapsari (Journal of Management and Business Innovations, 2025)
This study aimd to examine the extent of internet media use and its impact on sales growth among MSMEs in Tanjung Balai City. This type of research is a descriptive qualitative study using a qualitative triangulation approach, which integrates observation, semi-structured interviews, questionnaires, and documentation to strengthen data validity without conducting statistical tests. The results of the study indicate that optimal use of internet media results in an average increase in sales of 32% compared to the period before adoption. The most widely used media and contributing to this increase is Facebook social media. Other findings in this study suggest that MSME actors still lack a strategic understanding of how to utilize digital platforms effectively and other obstacles related to limited technological infrastructure and high market competition, which hinder product visibility and consumer engagement. These results indicate the need for capacity building initiatives and digital literacy training to help MSMEs maximize the benefits of internet media for business growth. Keywords: Digital Marketing, MSMEs, Tools